(untitled) (Research, Society and Development, 2022)
Introduction: Urgency and emergency are considered priority situations that require fast and effective care in a short period of time. The teaching strategies carried out by professors are essential to enhance the learning process. The application of active methodologies in health education favors pedagogical practice with excellence. The general objective of the study is to analyze, through the literature, the main active methodologies used in the teaching of urgency and emergency discipline in the Nursing course. Methodology: The study was carried out through an integrative review (IR), which followed the six phases. Results and Discussion: Eleven primary studies were used for this review. In this scenario, the use of active methodologies in the educational and professional scope enhance the problematization of discussions about teamwork, as well as communication for the construction of teamwork. Final considerations: The findings of this review are relevant for health professionals, especially nurses who teach and work in urgency and emergency.